Analysis of Hyperbolic Language in Tourist Advertisement E-Brochures of Indonesian Tourist Destinations - Rofifah, Huwaida; Merrita, Diah (e-LinguaTera, 2025)
The research is about the analysis of hyperbolic language in tourist advertisement e-brochures of Indonesian tourist destinations. The purpose of this research is to find out the forms of hyperbolic language presented in e-brochures from Indonesia.travel that consists of Indonesian tourist destinations, as well as to find out the frequency of each hyperbolic form found and the total of it. The forms of hyperbolic language used are based on Claridge (2011) theory. The researcher used descriptive case study to find out forms of hyperbolic languages that are present in e-brochures of Indonesian tourist destinations and provide a description in order to give an understanding of how the hyperbolic language is used and how it contributes to the appeal and persuasion to the readers. The data were collected from indonesia.travel, which is an official website of the Ministry of Tourism, Republic of Indonesia, where e-brochures of Indonesian tourist destinations are provided. In conclusion, out of the 6 e-brochures, the researcher found a total of 198 hyperboles. There were 69 single-word hyperboles, 43 phrasal hyperbole, 31 clausal hyperbole, 31 superlative hyperbole, 15 numerical hyperbole, and 9 comparison hyperbole. Repetition is not found at all.